2017
DOI: 10.15406/acp.2017.02.00015
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasitic Infection and Body Mass Index among School Children in Oshodi Lagos Nigeria

Abstract: Background: Intestinal parasitic infections are still major public health problems in the world, particularly in developing countries. These parasitic infections have adverse effect on the health status of individuals particularly children. Objective: The study is designed to determine the effect of nutritional status on the prevalence of intestinal parasites among the school children in Oshodi, Lagos State Nigeria between June and August 2014. Methods: A total of consented 386 from seven public primary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Oppositely, hookworms and S. stercoralis were not found among schoolchildren in the current study. This is similar to reports from previous studies (Al-Qobati et al, 2012; bin Mohanna et al, 2014 ; MB, 2017 ; Singh Khadka et al, 2019 ; Sitotaw et al, 2020 ). However, hookworms and S. stercoralis have low prevalence rates in Ibb among schoolchildren, reporting 1.2 % and 0.8 % prevalence rates, respectively ( Alsubaie et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Oppositely, hookworms and S. stercoralis were not found among schoolchildren in the current study. This is similar to reports from previous studies (Al-Qobati et al, 2012; bin Mohanna et al, 2014 ; MB, 2017 ; Singh Khadka et al, 2019 ; Sitotaw et al, 2020 ). However, hookworms and S. stercoralis have low prevalence rates in Ibb among schoolchildren, reporting 1.2 % and 0.8 % prevalence rates, respectively ( Alsubaie et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…This could a result of the combine effects of the parasites isolated (Naing et al, 2013). Numerous epidemiological studies have demonstrated an association between STH infections and nutritional status (Ajayi et al, 2017). Children with mixed or moderate to heavy STH infections frequently experience more severe effects than single-specie or light infection (Mascarini-Serra, 2011).…”
Section: Figure 1: Overall Prevalence Of Parasitic Infection In the S...mentioning
confidence: 99%
“…For assessing the nutritional status of populations, especially children in underdeveloped nations, anthropometry has evolved into a helpful instrument. Similarly, children's nutritional state is the best gauge of their overall well-being (Ajayi et al, 2017). Nigeria remained the African country with the highest burden and endemicity of intestinal helminthiasis, with children residing primarily in rural and semi urban areas constituting a greater percentage (Anunobi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, children born to mothers infected with these helminths during pregnancy are at elevated risk of infection during their early years [6]. Practices such as geophagy, open defecation, the use of leaves and paper for hygiene, nail-biting, and walking barefoot further contribute to the persistently high prevalence of STH infections [7][8][9]. Sub-Saharan African nations, notably Nigeria, bear the brunt of STH infections, with significant disparities across regions.…”
Section: Introductionmentioning
confidence: 99%